Ativismo judicial: uma análise fenomenológica da historicidade da interpretação do texto jurídico - Serva Neto, Raul Diegues (2017)
The purpose of this study was to identify, throughout the historicity of the interpretative practices, evaluation criteria for a legal decision analysis, using ADPF 187 (marijuana gait) as the application criterion for the elaborated construction. The starting question was: what makes it possible to make relevant statements about the Law? It was observed as the dissertation hypothesis, if the judicial decision presents transgressions of validity allowing for an interpretative discretion, then it may reveal a greater propensity to be an activist. In order to answer the initial question, the study was based on the following methodology: from the contribution of the hermeneutical turn in the approach to the analysis of the ADPF 187 decision, which makes it an activist legal decision; from the Heideggerian phenomenological method, by developing a three-step approach: (1) the phenomenological reduction, which promotes the shift from the perspective of the being towards the being; 2) the deconstruction of traditional concepts, which promotes masks in phenomena; 3) and construction, which shows itself as an appropriation of what has been forgotten, in which the access to the being is sequenced and the definition of its modes of being from the being. After the development of the methodology, the development of the Dworkin aesthetic hypothesis was elaborated from the Schools of Legal Hermeneutics, in which, throughout the historicity of this discussion, the first criterion resided in the will of the legislator, although this is a body disempowered; the will of the law is also not enough, because the law has no will, and it can be attributed to it; the legally protected interest can be considered a criterion of validity, which depends more on the conflicting reading of Law than on Law itself; normativism assigns either a policy decision or a recognition rule the interpretation validity, which, in a way, seeks outside the Law a criterion of validity for interpretations, or because it resides within a metaphysically conceived frame based on a hypothetical norm, or based on the recognition of all; finally, the dependence on the recognition of a legal proposal by the courts was added. None of these validity criteria is conceived from the Law itself, they generally attribute the validity of interpretations to facts. Next, the view is taken that the contributions on the Law validity unfold in the debate on the interpretative positions of the constitutional courts. Such an appeal is made for the purpose of avoiding moral or political correctness of the law. It discusses the multiple concepts of judicial activism, considering it as a contested and highly controversial concept, and then analyzes the assumptions of such concepts. Therefore, a study of the validity of the reading assumptions that support the comprehension of the validity of the reading of freedom of expression in its instrumental or constitutive bias was sought, based on the study of ADPF 187 (marijuana march) decision. This theoretical research constituted a critique of uncritical legal interpretation. He presented as a means of showing the forgetfulness of being-thus, the means of knowing the foundation and meaning of this being-thus.